Developmental database for phenology models: related insect and mite species have similar thermal requirements - Jarošík, Vojtěch; Honěk, Alois; Magarey, Roger D; Skuhrovec, Jiří (Journal of economic entomology, 2011)
Two values of thermal requirements, the lower developmental threshold (LDT), that is, the temperature at which development ceases, and the sum of effective temperatures, that is, day degrees above the LDT control the development of ectotherms and are used in phenology models to predict time at which the development of individual stages of a species will be completed. To assist in the rapid development of phenology models, we merged a previously published database of thermal requirements for insects, gathered by online search in CAB Abstracts, with independently collected data for insects and mites from original studies. The merged database comprises developmental times at various constant temperatures on 1,054 insect and mite species, many of them in several populations, mostly pests and their natural enemies, from all over the world. We show that closely related species share similar thermal requirements and therefore, for a species with unknown thermal requirements, the value of LDT and sum of effective temperatures of its most related species from the database can be used.
Keywords: druhová specificita; Animals; biologické modely; Temperature; Female; Models, Biological; mužské pohlaví; zvířata; Male; hmyz; Species Specificity; roztoči; teplota; Insecta; ženské pohlaví; Mites